Innovative vector of development of modern healthcare system in Kazakhstan: organizational and economic mechanisms and extrapolation of foreign experience - Smailov, B.T.; Andarova , R.K. (BUKETOV BUSINESS REVIEW, 2019)
The article is devoted to the study of organizational and economic mechanisms of innovative development of the healthcare system of Kazakhstan on the basis of extrapolation of effective foreign experience. The key problems of innovation in various fields of medicine are highlighted. The mechanism of technology transfer, the practical state with the use of advanced technologies is relevant. The mechanism of the public-private partnership for long-term financing of healthcare and providing positive animation is proved. In the field of innovations in the organization of healthcare, the basic mechanism is the introduction of compulsory social health insurance, the specifics of which are analyzed in the article. In the field of regulation of procedures relevant and modern is the introduction of information elements. Their structure and mechanism are also discussed in the present article. The article also considers the organization of clusters of medical innovations. The result of the implementation of the cluster approach should be an increase in productivity and innovation activity of enterprises belonging to the cluster, as well as an increase in the intensity of development of small and medium-sized businesses, which can significantly strengthen the innovative component of its activities in the promotion of the most effective medical technologies.